Comparative Study of Combined Steroid-Antibiotic Aural Pack versus Antibiotic Drop in Otitis Externa - Jayanta Saha; Debabrata Biswas; Tithi Debnath; Subhadeep Chowdhury (Bengal Journal of Otolaryngology and Head Neck Surgery, 2024)
INTRODUCTION Otitis externa is an inflammatory condition of the skin of the external auditory canal that is characterized by generalized edema and erythema. It is a very common condition which is encountered in day to day outpatient services in the life of otolaryngologists. So treatment includes not only antibiotics and analgesics systemically but also aural packing for topical application . This study was performed to observe the effectiveness of treatment for relieving pain and edema by comparing steroid–antibiotic aural pack with antbiotic ear drop.